Transitions from Juridical to Empirical Statehood in Africa: A Case Study of Botswana and Somalia. - Jeng, Ndey Haddy (ADA University, 2013)
African states have been the subject of many studies and scholarly debates on state failure in the Third World with much focus on the causes and consequences of state failure in the continent. Theories presented focus on explanations ranging from the ethno linguistic fragmentations, political and state incapacity, economic /neopatrimonial explanations and legal explanations most of which do not tackle the issue of case variations within the continent. In this paper, I focus on the theory of Robert Jackson with his explanations of juridical and empirical statehood. I argue that even though African states inherited juridical (legal) statehood upon independence and this has impacted negatively on effectiveness of the state, the condition has not been stagnant for all states. There exists a post independence transition process to effective empirical statehood and there are varying outcomes to this process. Where some states like Botswana have succeeded, others like Somalia have failed. To find out the cause of these variations in outcomes I devise a method of using existing theories of ethnic fragmentation and congruence of pre-colonial and post-colonial institutions to test their causal value on the varying outcomes of the transition process from juridical to empirical statehood. By making such an analysis, I reach the conclusion that Identity whether ethnic or national does not hold a direct causal link or determine the varying outcomes of success or failure of states in the transition process to effectiveness. It is rather a contingent factor. I conclude that it is the pre and existing political culture within the state that determines the outcome of the post independence transition process. Where the political culture is similar to that of the modern Weberian state, the outcome of transition becomes successful and vice versa.
Keywords: Public and International Affairs; Botswana--Social conditions.; Somalia--Social conditions.